Managerial coaching: a literature review - Paul Lawrence (International Journal of Evidence Based Coaching and Mentoring, 2017)
The term managerial coaching is often used to describe the leader’s role in developing people, but views differ as to the optimal process by which this is achieved. Although managerial coaching is often regarded as a ‘cut down’ or simplified version of external coaching, it is suggested here that the role of the managerial coach is, in many respects, more challenging than that of the external coach, such that managerial coaching may be more usefully regarded as a discrete and equally demanding discipline, albeit related to external coaching. The article concludes with suggestions for future research, suggesting that a systemic approach is likely to prove more fruitful than traditional approaches focussed on individual behaviours.